Comparison of postoperative analgesia and side effects in pediatric laparoscopic surgery with morphine and nalbuphine - Jia Chen; Cheng-Yu Wang; John Wei Zhong; Yu-Hang Cai; Jianmin Zhang; Fang Wang; Mazhong Zhang; Hongbin Gu; Hong-Yu Ma; Zhen Wang; Junzheng Wu; Hua-Cheng Liu (iScience, 2024)
Summary: There is currently no consensus on the optimal perioperative pain management strategy involving specific opioids. This study aims to compare the postoperative analgesia, the associated side effects between nalbuphine and morphine in children undergoing laparoscopic surgery. One hundred ninety children were randomly assigned to nalbuphine (0.2 mg/kg) or morphine (0.2 mg/kg). Nalbuphine’s analgesic effect was non-inferior to morphine, with similar total rescue analgesic consumption during PACU stay (0.03 ± 0.05mg vs. 0.04 ± 0.06 mg, p > 0.05). Nalbuphine group had a lower incidence of respiratory depression (RR ≤ 10/min) (4.8% vs. 38.6%, p < 0.001), PONV (2.4% vs. 18.1%, p = 0.002), and pruritus (0% vs. 16.9%, p < 0.001) than morphine. Additionally, nalbuphine showed a shorter laryngeal mask airway removal time (13.9 [12.7, 15.1]) compared with morphine (17.0 [15.1, 18.9], p = 0.011). Nalbuphine provides equipotent analgesia with significantly lower incidences of respiratory depression, PONV, and pruritus compared with morphine in pediatric laparoscopic surgery.